2013
DOI: 10.1002/glia.22615
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of activity of P2X7 receptor by its splice variants in cultured mouse astrocytes

Abstract: Of purinergic receptors, P2X7 receptor (P2X7R, defined as a full-length receptor) has unique characteristics, and its activation leads to ion channel activity and pore formation, causing cell death. Previously, we demonstrated that P2X7R expressed by nonstimulated astrocyte cultures obtained from SJL-strain mice exhibits constitutive activation, implying its role in maintenance of cellular homeostasis. To obtain novel insights into its physiological roles, we examined whether constitutive activation of P2X7R i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…13) In contrast to the case of astrocytes, neurons in acute slices were not constitutively activated under non-stimulated resting conditions, and this was the same with their primary cultures. 5,13) Although detail mechanism underlying this is unclear, this difference is considered to be due to the difference in cell types, implying different roles of P2X7Rs in astrocytes and neurons. SJL mice are known to exhibit extreme aggression, 29) differing from ddY ones.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…13) In contrast to the case of astrocytes, neurons in acute slices were not constitutively activated under non-stimulated resting conditions, and this was the same with their primary cultures. 5,13) Although detail mechanism underlying this is unclear, this difference is considered to be due to the difference in cell types, implying different roles of P2X7Rs in astrocytes and neurons. SJL mice are known to exhibit extreme aggression, 29) differing from ddY ones.…”
Section: Discussionmentioning
confidence: 81%
“…The finding that P2X7Rs in in vivo tissue astrocytes, but not neurons, exhibit constitutive activation, is identical to that in in vitro cell culture systems of astrocytes and neurons. 5,12,13) Therefore, it is suggested that under in vivo non-stimulated resting conditions, astrocytic P2X7Rs play roles in the maintenance of brain homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two hypothetical mechanisms, namely the gating model and the Pannexin-1 model, have been proposed [3] . In the gating model, pore dilation resulted from longterm ATP action, which leads to additional conformational change [118][119][120][121][122][123][124] . While in the Pannexin-1 model, the conformational changes of the P2X receptor resulted in allosterism of an auxiliary protein coupled with the P2X receptor, such as Pannexin-1, permitting molecules to enter cells through those proteins [125,126] .…”
Section: Questions To Be Answeredmentioning
confidence: 99%